2021
DOI: 10.18553/jmcp.2021.21164
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of cemiplimab vs pembrolizumab for treatment of advanced cutaneous squamous cell carcinoma

Abstract: BACKGROUND: Most cutaneous squamous cell carcinomas (CSCCs) can be treated with surgical excision or radiation; however, approximately 1% of patients develop advanced disease. In 2018, the FDA approved cemiplimab-rwlc as the first programmed cell death-1 (PD-1) monoclonal antibody for the treatment of patients with metastatic CSCC or locally advanced CSCC who are not candidates for curative surgery or curative radiation. In June 2020, pembrolizumab, another PD-1 monoclonal antibody, was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The choices of statistical distributions and correlations in probabilistic sensitivity analyses should be fully documented and justified [ 9 ]. Scenario analyses are also recommended where possible since several CUAs conducted these practices [ 34 , 56 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The choices of statistical distributions and correlations in probabilistic sensitivity analyses should be fully documented and justified [ 9 ]. Scenario analyses are also recommended where possible since several CUAs conducted these practices [ 34 , 56 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The antiprogrammed death ligand 1 (PD‐1) drug Keytruda (pembrolizumab) has been approved by the US Food and Drug Administration (FDA) for CSCC treatment. 3 Another anti‐PD‐1 antibody drug Libtayo (Cemiplimab‐rwlc) has shown good efficacy in the treatment of skin squamous cell carcinoma 4 ; thus the FDA has approved Libtayo for metastatic CSCC that is not suitable for surgery or radiotherapy. 5 The results of its phase II clinical trial showed that 34% of patients receiving immunotherapy have been significantly improved.…”
Section: Introductionmentioning
confidence: 99%